ChemInform Abstract: Rhodium or Ruthenium‐Catalyzed Oxidative C—H/C—H Cross‐Coupling: Direct Access to Extended π‐Conjugated Systems. Issue 20 (25th April 2013) - Dong, Jiaxing; Long, Zhen; Song, Feijie; Wu, Ningjie; Guo, Qiang; Lan, Jingbo; You, Jingsong
Abstract This method is highly chemo‐ and regioselective and applicable to a broad variety of heteroarenes.